PREVENTION AND TREATMENT OF FUNCTIONAL DISORDERS OF GASTROINTESTINAL TRACT IN INFANTS AND YOUNG PRE-SCHOOL CHILDREN - M.Yu. Denisov (Педиатрическая фармакология)
The article showcases key reasons for functional disorders of the intestinal tract in breast-fed and formula-fed infants. It describes from a practical standpoint modern approaches to identifying causes and administration of remedial treatment for this category of patients. The main aspects in prevention of this functional pathology are characterised. Key words: children, functional defecation disorders, constipation, remedial treatment. (Pediatric Pharmacology. – 2010; 7(2):91-95)